The Future of Hydroelectricity from Patagonia? (Americas)
The article focuses on HidroAysén, a hydroelectric project of Endesa Chile planned for Pascua, one of the two rivers in southern Chile. The $4 billion scheme involves the construction of five large dams designed to produce 2,750 megawatts of electricity to boost Chile's power supply by 20 percent. Hernán Salazar, chief executive officer (CEO) of HidroAysén, relates how the scheme will protect Chile's energy security. It explains why ecologists are opposing the scheme. It describes the outlook of Chileans on the project.